Performance Analysis of Granular Computing Model on the Basis of S/W Engineering and Data Mining - Rajashree Sasamal; Rabindra Kumar Shial (Institute of Advanced Engineering and Science, 2012)
Granular Computing is not only a computing model for computer centered problem solving, but also a thinking model for human centered problem solving.Some authors have presented the structure of such kind models and investigated various perspectives of granular computing from different application point of views. In this paper we discuss the archeitectue of Granular computing models, strategies, and applications. Especially, the perspectives of granular computing in various aspects as data mining and phases of software engineering are presented, including recquirement specification system analysis and design, algorithm design,structured programming,software tesing.AI is used for measuring the three perspective of Granular Computing model. Here we have discovered the patterns in sequence of events has been an area of active research in AI. However, the focus in this body of work is on discovering the rule underlying the generation of a given sequence in order to be able to predict a plausible sequence continuation ( the rule to predict what number will come next, given a sequence of numbers).DOI: http://dx.doi.org/10.11591/ij-ai.v1i4.1181